2016
DOI: 10.1101/081281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the accuracy of genomic prediction of growth and wood traits in twoEucalyptusspecies and their F1hybrids

Abstract: Background: Genomic prediction is a genomics assisted breeding methodology that can increase genetic gains by accelerating the breeding cycle and potentially improving the accuracy of breeding values. In this study, we use 41,304 informative SNPs genotyped in a Eucalyptus breeding population involving 90 E.grandis and 78 E.urophylla parents and their 949 F 1 hybrids to develop genomic prediction models for eight phenotypic traits -basic density and pulp yield, circumference at breast height and height and tree… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 68 publications
2
5
2
Order By: Relevance
“…When the number of markers increases the computational time for Bayesian method took longer time to converge. Therefore, we also support the proposal that GBLUP is an effective method in providing the best compromise between computational time and prediction efficiency if there are no major gene effects [4,42].…”
Section: Different Gs Methods Show Similar Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…When the number of markers increases the computational time for Bayesian method took longer time to converge. Therefore, we also support the proposal that GBLUP is an effective method in providing the best compromise between computational time and prediction efficiency if there are no major gene effects [4,42].…”
Section: Different Gs Methods Show Similar Resultssupporting
confidence: 79%
“…In our study, heritabilities for wood quality traits were higher than those for tree height, which is expected and agrees with previous reports for Norway spruce [1,28]. Tan et al [4] reported that heritability estimates obtained from GBLUP were higher than those from ABLUP for growth and wood quality traits in Eucalyptus. In contrast, Lenz et al [15] and Gamal EL-Dien et al [12] reported that heritability estimates obtained from GBLUP were lower than those from ABLUP for similar growth and wood quality traits in black spruce and interior spruce (Picea glauca [Moench] Voss  Picea engelmannii Parry ex Engelm.).…”
Section: Heritability Estimatessupporting
confidence: 93%
See 3 more Smart Citations